PENYULUHAN TENTANG ALUR PELAYANAN IGD/UGD DI RUMAH SAKIT DI MESJID AR-RAUDHAH JLN.KARYA BAKTI, KELURAHAN BAMBU KUNING, KECAMATAN TENAYAN RAYA, KOTA PEKANBARU - Tonis, Marian; Firdaus, Muhammad; Suryandartiwi, Wiwik; Yuliana, Anastasya Shinta (LPPM Universitas Awal Bros, 2023)
The Emergency Department is one of the units in a hospital that provides initial treatment of patients, according to the level of emergency. The difference between ER and ER. ER stands for emergency department, while ER stands for emergency installation. Both the ER and the ER have the same handling principles. Both provide appropriate and prompt treatment for emergency or life-threatening medical conditions. A screening officer will sort patients into triage groups. The triage group consists of red triage, yellow triage, green triage, and black triage. The action of ER / ER services starts from the patient coming until the patient is finished. Therefore, to inform the local community about the flow of emergency room services, we conduct counseling. After all these stages were carried out, a planning of counseling activities for the flow of emergency room services was obtained at the Ar-Raudhah mosque.